1992
DOI: 10.1017/s0890037x00036538
|View full text |Cite
|
Sign up to set email alerts
|

Alfalfa (Medicago sativa) Response to Simulated Herbicide Spray Drift

Abstract: ‘Vernal’ alfalfa response was evaluated when chlorsulfuron, thifensulfuron, 2,4-D, glyphosate, bromoxynil, and selected combinations of those herbicides were applied at rates simulating spray drift during the fourth trifoliolate leaf stage following the first cutting in 1990 and 1991. The order of phytotoxicity was 2,4-D > chlorsulfuron > thifensulfuron > glyphosate > bromoxynil. By the end of each growing season, alfalfa had recovered from injury caused by all herbicides except the highest rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 8 publications
2
25
0
Order By: Relevance
“…Since S. arvensis and six other species of the Brassicaceae family appear on the label as species controlled by metsulfuron methyl, injury was anticipated for S. arvensis. The magnitude of the effect, especially on the reproductive parts at a rate below 1% of the label rate, was, however, unexpected, although similar results were found with chlorsulfuron on a wide range of species of the same families [10,16–19]. Furthermore, turnip ( B. rapa ) was adopted as a bioassay species for detection of residual effects of metsulfuron methyl and other sulfonylureas, on different types of soil [9], demonstrating the high sensitivity of this family to metsulfuron methyl and sulfonylureas in general.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Since S. arvensis and six other species of the Brassicaceae family appear on the label as species controlled by metsulfuron methyl, injury was anticipated for S. arvensis. The magnitude of the effect, especially on the reproductive parts at a rate below 1% of the label rate, was, however, unexpected, although similar results were found with chlorsulfuron on a wide range of species of the same families [10,16–19]. Furthermore, turnip ( B. rapa ) was adopted as a bioassay species for detection of residual effects of metsulfuron methyl and other sulfonylureas, on different types of soil [9], demonstrating the high sensitivity of this family to metsulfuron methyl and sulfonylureas in general.…”
Section: Discussionmentioning
confidence: 89%
“…Metsulfuron methyl can also prevent the development of seeds and reduce seed weight [6,14,15]. Chlor‐sulfuron, another sulfonylurea herbicide frequently used in the United States on cereals for the control of several broad‐leaf plants, has been shown to cause a substantial reduction in yield [16,17] and seed output in several species [18–20]. Sulfonylurea sprayed on grain crops growing in the vicinity of some orchards in the United States may also have been implicated in low orchard yields [17,19].…”
Section: Introductionmentioning
confidence: 99%
“…For some situations there may be a need for input from atmospheric chemists, meteorologists and other specialists, as well as chemical analyses to support observations of symptoms. 35,36,39 Assessment for visible symptoms on plants is simple to perform but difficult to quantify. This is especially true when untreated plants for comparison are not readily available.…”
Section: Visual Assessmentsmentioning
confidence: 99%
“…19 Newsom & Shaw48 reported that, while soybean height for several cultivars was reduced by soilapplied chlorimuron in high moisture regimes, this did not necessarily translate into yield reductions. In some circumstances sections of plant height have been measured, such as lateral branch growth or internode length, to assess sulfonylurea exposure.50,51 The number of nodes per plant has not been reported to be a †ected by sulfonylurea exposure.48 Al-Khatib et al 17 found that, for a perennial forage species (i.e. alfalfa), plant height measurements following foliar sulfonylurea treatment were useful for assessing regrowth after repeated harvests.…”
Section: Plant Heightmentioning
confidence: 99%
“…Symptomology following exposure to phenoxyacetate herbicides has been described in nontarget plants [4,20]. Studies in Washington have examined the effects of dilute herbicide sprays (0.3-0.01 of the maximum use rates) on grapes, alfalfa, roses, and sweet cherries [21][22][23][24]. Recently published studies noted effects on reproductive physiology in sweet cherry [25,26].…”
Section: Introductionmentioning
confidence: 99%